A systematic review of economic evaluations for the pharmaceutical treatment of chronic lymphocytic leukemia and acute myeloid leukemia. Issue 9 (2nd September 2022) - Gao, Lan; Nguyen, Dieu; Lee, Peter
ABSTRACT: Introduction: No recent full-text-based systematic review has been published to examine economic evidence around acute myeloid leukemia (AML) or chronic lymphocytic leukemia (CLL) treatment. We aimed to perform a systematic review in this area. Areas covered: This review entailed searches in three main databases for economic evaluations of treatment in AML or CLL. After title and abstract screening, two reviewers examined all the citations in full text. Any disagreement between the two reviewers was resolved through discussion with the third reviewer. We used predesigned tools for data extraction, including study characteristics, primary results and conclusions. The quality of included studies was assessed. Expert opinion: The majority of the studies adopted the modeling approach to estimate the long-term cost-effectiveness of the treatment from the healthcare system payer's perspective. Most studies concluded that the evaluated treatment interventions for untreated or refractory AML or CLL were cost-effective across various jurisdictions. The EQ-5D, followed by time trade-off and standard-gamble, was the most commonly used outcome measure to derive the utility weights associated with each health state. Clear justifications for the choice of modeling technique are recommended for future studies. Collecting the health-related quality of life outcome using a common instrument over the clinical trial could aid the comparability among economic studies.